Icon of evil : Hitler's mufti and the rise of radical Islam - Dalin, David G., 1949- 1949- (Random House, 2008)
In 1921, the beneficiary of an appointment the British would live to regret, Haj Amin al-Husseini became the mufti of Jerusalem, the most eminent and influential Islamic leader in the Middle East. For years, al-Husseini fomented violence in the region against the Jews he loathed and wished to destroy. Forced out in 1937, he eventually found his way to the country whose legions he desperately wished to join: Nazi Germany. Here, with new and disturbing details, David G. Dalin and John F. Rothmann show how al-Husseini ingratiated himself with his hero, Adolf Hitler, becoming, with his blonde hair and blue eyes, an "honorary Aryan," while dreaming of being installed Nazi leader of the Middle East. Al-Husseini would later recruit more than 100,000 Muslims in Europe to fight in divisions of the Waffen-SS, and obstruct negotiations with the Allies that might have allowed four thousand Jewish children to escape to Palestine. --from publisher description